The Study of Literature and Religion - Jasper, D. author. aut Link
XII, 158 p.
Keywords: An exploration of the relationship between literature and religion, which adopts an interdisciplinary approach, aiming to provide an introduction to the variety of ways in which literature, literary theory and theology are related.